Pengaruh Pembelajaran Tematik dengan Menerapkan Pendekatan Lingkungan terhadap Pengetahuan Siswa Sekolah Dasar Negeri Seluma tentang Lingkungan Sahabat Kita - Gunawan, Ansyori; Dadi, Sri; Anggraini, Dwi (UNIB Press, 2019)
The purpose of this study is to determine the effect of thematic learning by applying an environmental approach to the knowledge of Seluma Primary-School students about the Our Friends Environment. The research used is the only matching pretest-posttest control group design. The populations are all grade V students of SDN Seluma in the academic year 2017/2018. The research samples are grade V students of SDN 01 and SDN 13 Seluma. The instrument used is a test sheet to measure students' knowledge about the environment of our friends. The results of the research data are analyzed inferentially by independent sample t-test. The results of the study obtained a significance value (2- tailed) is lower than 0.025. The conclusion of this study is that there is a significant influence of thematic learning by applying an environmental approach to the knowledge of SDN Seluma students about the environment of our friends.